Dynamika sytuacji zawodowej absolwentów pedagogiki Uniwersytetu Zielonogórskiego. Raport z badań absolwentów roczników 2005-2013 = The dynamics of professional situation of the graduates of pedagogy at the University of Zielona Góra. A research report on graduates of 2005-2013 - Kołodziejska, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents chosen results of research carried out twice in the field of professional careers of graduates of pedagogy in the Pedagogy, Sociology and The Health Science Departments at the University of Zielona Góra. The first edition of the research, completed in 2010, included the graduates of 2005-2009. The second edition of the research completed in 2013 diagnosed the following graduates of pedagogy (2010-2013) by means of the same method and tool.
Keywords: Uniwersytet Zielonogórski; absolwenci; badania; monitorowanie losów absolwentów